Pengaruh Sifat Inovasi Teknologi terhadap Tingkat Penerapan, Produktivitas dan Pendapatan Usahatani Padi di Desa Cililin - Ning Srimenganti; Tito Hardianto (Ma'soem University, 2023)
This study aims to determine the influence of the innovative nature of Integrated Crop Management (PTT) technology and its effect on the productivity and income of Rice farming businesses. This research used a survey method for farmers who applied PTT in Cililin Village, Cililin District, West Baandung Regency. The example assignment technique used was simple random and obtained by 40 respondent farmers. The form of research is verifiable and hypotheses are analyzed using multiple linear regression analysis and chi square test. The results of the study obtained an overview of the application of PTT technology as a whole with an achievement rate of 82.07% with very good criteria, the productivity of rice farming for farmers who apply PTT technology empirically reaches an average of 6,412 kg / ha, and empirically the level of achievement of rice farming income averages Rp. 11,987,886 /ha.